ANALISIS MANAJEMEN PENGADUAN KANAL PENGADUAN â€œSAPA MBAK ITAâ€ KECAMATAN TEMBALANG - Maya Silvia; Budi Puspo P.; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This research ia focused on the implementation of complaint management implemented by the Tembalang District Government on complaints sent by the public through the